Clusters, nanoclusters and nanozoli metals in catalysis disproportionation of free radicals: mechanisms, aspect himmotolohiyi - Ковтун, Г.О. (Proceedings of National Aviation University (archive), 2009)
In the article the chemmotology’s aspect of role of clusters, nanoclusters and to the nanozole of metals, is considered in the catalysis of disproportionation of free radicals.